Biography as Literature of Life: The Intellectual and Social Network of Professor Kamaldeen Balogun in Ago-Iwoye - Hashimi, A. O. (NIU Journal of Social Sciences; Vol 7 No 2 (2021): KIU Journal of Social Sciences, Vol. 7 No. 2, June 2021, 2021)
This paper is intended to highlight the contributions and achievements of Professor Kamaldeen Balogun, an intellectual figure who blazes the trail of the modern renaissance of Arabic and Islamic studies in Ago-Iwoye. The paper therefore to a large extent, highlights his outstanding contributions to the growth of Islam in Ago-Iwoye in particular and Ijebuland in general through his academic career and his services to the community. Therefore, this paper focuses on the biography of Professor Kamaldeen Balogun . The study adopted historical descriptive method. Professor Balogun has trained many scholars and authored many works that have impact on the lives of many people within his reach and beyond.  His live in Ago-Iwoye influences many lives and promoted the image of the town in the outside world. Thus his ways of life, contributions and achievement have served as motivating and inspiring factors to the Muslims and younger generation of scholars and researchers. Keywords:  Ago-Iwoye, Biography, Intellectual Reform and Literature of Life